Predicting Multi-Epitope Peptide Cancer Vaccine from Novel TAA Topo48 - Tirta Setiawan; Rizarullah Rizarullah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
Cancer is one of the most lethal diseases. Recently, cancer immunotherapy has a tremendous achievement in cancer treatment. A certain number of cancer based epitope vaccines with different moiety have been discovered. In japan, several clinical tests of cancer based epitope vaccine derived from tumor associated antigens (TAAs) are now ongoing or have recently been completed. a novel of TAAs potentially as cancer vaccine have been retrieved from a fragment weighed 48kDa derived from human DNA-topoisomerase 1 (TOP1) called Topo48. Therefore, it is still critical to discover a derived Topo48 epitope based cancer vaccine. Immuno-informatics considered as a methods noted to have better accuracy to design promising vaccine candidates. Here, continuous and discontinuous B-cell epitopes following with CTL epitopes and their docking interaction to major histocompatibility complex (MHC) class I Human Leukocyte Antigens (HLA)- A0201 were predicted. Kolaskar-Tongaonkar’s, Emini’s, Karpus-Schulz’s, and Parker’s methods were used to predict continuous B-cell epitopes while ElliPro was used for prediction of discontinued B-cell epitopes. Those considered methods marked to have better accuracy to design promising vaccine candidates. Similarly, CTL epitopes was also predicted by using NetCTL server and the best candidates were further investigated their binding affinity by mean of PEP-FOLD3, PatchDock rigid-body docking server, and FireDock server. Total 27 continuous epitopes and 7 discontinuous B-cell epitopes were predicted. In the other hand, 9 peptides were predicted as CTL epitopes. Whereas, three predicted CTL epitope in range 263MLDHEYTTK27, 755AIDMADEDY763, 715ALGTSKLNY724) exhibited good interactions to HLA-A0201. Moreover, we also found residues His266, Thr270, Ala755, Tyr723, Thr718, Ser719, Lys720 from Topo48 and residues Thr163, Asp757, His70, Glu63 from HLA- A0201 were indicated to be antigenic. Ultimately, our proposed continuous/discontinuous B-cell epitopes, and also CTL epitopes can be potential vaccines for cancer immunotherapy.